The Effect of Bullying toward early Age Children's Mental Health - Felayati, Felayati; Fatimah, Fatimah; Rahmi, Azvi; Zeki, Serpuadi (Journal of Islamic Early Childhood Education, 2023)
Bullying is an act or behavior that is carried out by means of hurting physically, verbally or emotionally/psychologically by a person or group who feels physically or mentally weaker repeatedly without any resistance with the aim of making the victim suffer. Bullying behavior at Harapan Bunda can create an environment that is less supportive of children's development, both physically and mentally. Bullying behavior that occurred at Harapan Bunda was in the form of physical and non physical/verbal. Bullying arises because of misunderstandings and small problems that have an impact on the mental health of the victim. Bullying must be avoided because it has an impact on the mental health of early childhood. This can be seen from the fact that there are still young children who have had post-traumatic stress since childhood, anxiety, bipolar disorder. experienced by young children. The method used in this research is quantitative with non-random sampling because all populations are used as samples. With a total sample of 23 people. The result was found to be 0.078 or 7.8%. So bullying has a positive effect on mental health. This effect is also strengthened by a significance test of 0.000 less than 0.00.